1966
DOI: 10.1107/s0365110x66003359
|View full text |Cite
|
Sign up to set email alerts
|

A refinement of the crystal structure of zinc molybdenum(IV) oxide, Zn2Mo3O8

Abstract: Counter intensity data for zinc molybdenum(IV) oxide, Zn2Mo3Os, have been collected and a refinement of the structure has been carried out. The new data are consistent with space group P63mc; cell dimensions are a= 5"759, c= 9.903/~. The refined structure confirms the presence of triangular groups of bonded molybdenum ions. The oxygen coordination scheme -octahedral (with edge sharing) around molybdenum ions, octahedral for half the zinc ions and tetrahedral for the other half-is also confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(26 citation statements)
references
References 2 publications
5
21
0
Order By: Relevance
“…The members of this group were prepared and examined systematically by McCarroll, Katz & Ward (1957) who reported that the compounds were isostructural because of the similar characteristics of their X-ray powder diffraction patterns; they presented the results of structure determinations on Zn2Mo30 8 and Mg2Mo30 8. Later a refinement of the structure was accomplished by Ansell & Katz (1966) on Zn2Mo3Os, confirming the previously reported structural features. The result is used as the basis for the present work on Fe2Mo308 (kamiokite).…”
supporting
confidence: 71%
“…The members of this group were prepared and examined systematically by McCarroll, Katz & Ward (1957) who reported that the compounds were isostructural because of the similar characteristics of their X-ray powder diffraction patterns; they presented the results of structure determinations on Zn2Mo30 8 and Mg2Mo30 8. Later a refinement of the structure was accomplished by Ansell & Katz (1966) on Zn2Mo3Os, confirming the previously reported structural features. The result is used as the basis for the present work on Fe2Mo308 (kamiokite).…”
supporting
confidence: 71%
“…showing this behaviour (Cotton, 1977), for its lowvalent chemistry is characterized by numerous metalmetal bonded compounds which contain Mo clusters of various sizes such as Mo 2 dumb-bells [MoCI 3 (von Schnering & W6hrle, 1963); MoS2CI 3 (Marcoll, Rabenau, Mootz & Wunderlich, 1974)], Mo 3 triangles [Zn2Mo3Os (Ansell & Katz, 1966); MoN (Vandenberg & Matthias, 1974); Mo3S7C14 (Marcoll, Rabenau, Mootz & Wunderlich, 1974)], Mo4 tetrahedra [GaMo4S s (Perrin, Chevrel & Sergent, 1975a;Vandenberg & Brasen, 1975); MoSBr (Perrin, Chevrel & Sergent, 1975b)1, Mo 5 square-pyramids {[ (n-C4H9)aN]2Mo5CI13 (J6dden, von Schnering & SchS.fer, 1975)} and Mo 6 octahedra [MoCI 2 (Sch~ifer, von Schnering, Tillack, Kuhnen, W6hrle & Baumann, 1967); Mo3Se 4 (Bars, Guillevic & Grandjean, 1973)1. Compounds with clusters containing more than six Mo atoms, however, have not been found so far, and neither have substances been reported in which more than one transition-metal cluster species occurs in the same compound.…”
Section: Introductionmentioning
confidence: 99%
“…OEt )20 (10) are shown inFigure 1and reveal a striking similarity to both the [Ti(0Et)" structure and the structures of isopoly and heteropolyacids of molybde num, tungsten and vanadium.…”
mentioning
confidence: 83%
“…In the mixed oxo alkoxides of formula Mo 3 (0)(0R) 10 where R = CH 2 -t-Bu and i-Pr, the Mo-Mo distance is 2.535 A (averaged) (23), which may be compared with Mo-Mo = 2.524(2) R (averaged) in Zn 2 Mo 3 0 8 (19,20). The coordination about the molybdenum atoms is similar, but not the same for these triangulo complex es as is shown in Figure 2.…”
Section: Structural Andmentioning
confidence: 99%
See 1 more Smart Citation